Anti-inflammatory Effects of Abdominal Vagus Nerve Stimulation on Experimental Intestinal Inflammation - Payne, Sophie C.; Furness, John B.; Burns, Owen; Sedo, Alicia; Hyakumura, Tomoko; Shepherd, Robert K.; Fallon, James B. (Frontiers in Neuroscience, 2019)
Electrical stimulation of the cervical vagus nerve is an emerging treatment for inflammatory bowel disease (IBD). However, cervical vagal nerve stimulation (VNS) can produce unwanted side effects. Here, we investigated whether stimulating the vagus nerve closer to the end organ has fewer off-target effects, while reducing intestinal inflammation. An electrode array was developed to stimulate and record vagal neural responses in rats. Acute VNS off-target experiment: The cervical and abdominal vagus nerves of anaesthetised rats (n=5) were acutely implanted with an electrode array, stimulation delivered (10 Hz; symmetric biphasic current pulse; 320 nC per phase) and changes to heart rate, respiration and blood pressure assessed. Chronic VNS efficacy experiment: The abdominal vagus nerve was chronically implanted with an electrode array. After 2 weeks, the intestine was inflamed with TNBS (2.5% 2,4,6-trinitrobenzene sulphonic acid), an established method for rodent models of IBD. Rats were randomly selected to receive therapeutic VNS (n=7; 10 Hz; symmetric biphasic current pulse; 320 nC per phase; 3 hours/day) or no stimulation (n=8) for 5 days. Stool quality, C-reactive protein in blood and histology of the inflamed intestine were assessed. VNS off-target experiment: Abdominal VNS had no effect (two-way RM-ANOVA: P>0.05) on cardiac, respiratory and blood pressure parameters. However, during cervical VNS heart rate decreased by 31 ± 9 beats/minute (P>0.05), respiration was inhibited and blood pressure decreased. VNS efficacy experiment: During the implantation period, electrically-evoked neural response thresholds remained stable (one-way RM ANOVA: P>0.05), and were below stimulation levels. VNS rats, compared to unstimulated rats, had improved stool quality (two-way RM ANOVA: P<0.0001), no blood in faeces (P<0.0001), reduced plasma C-reactive protein (two-way RM ANOVA: P<0.05) and a reduction in resident inflammatory cell populations within the intestine (Kruskal-Wallis: P<0.05). Abdominal VNS did not evoke off-target effects, is an effective treatment of TNBS-induced inflammation, and may be an effective treatment of IBD in humans.